2022
DOI: 10.1039/d2nj03813g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and transformation of calcium carbonate polymorphs with chiral purine nucleotides

Abstract: The biomineralization process in organisms produces better quality biominerals. The most promising approach is using proteins with differing amounts of amino acids in crystals to create biominerals. Calcium carbonate (CaCO3)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…Figure b confirms that the relative amount of vaterite increases with the concentration of added nucleotides (for full and indexed diffractograms, refer to Figure S2). We believe that this case corroborates previous reports, in which negatively charged organic molecules, when added to the precipitation solution of CaCO 3 , were shown to stabilize vaterite. It should be noted that the presence of nucleotides during precipitation induces a reduction in its crystallinity. The latter can be concluded from the observation that the background signal of the diffraction patterns, and especially the broad diffraction peak at low 2θ angles, intensifies with an increase in the amount of ATP and CTP (Figure S3).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure b confirms that the relative amount of vaterite increases with the concentration of added nucleotides (for full and indexed diffractograms, refer to Figure S2). We believe that this case corroborates previous reports, in which negatively charged organic molecules, when added to the precipitation solution of CaCO 3 , were shown to stabilize vaterite. It should be noted that the presence of nucleotides during precipitation induces a reduction in its crystallinity. The latter can be concluded from the observation that the background signal of the diffraction patterns, and especially the broad diffraction peak at low 2θ angles, intensifies with an increase in the amount of ATP and CTP (Figure S3).…”
Section: Resultssupporting
confidence: 91%
“…We showed that the presence of nucleotides during CaCO 3 growth promotes the formation of both ACC and vateritetwo of its metastable forms. While the effect of nucleotides on the resulting CaCO 3 polymorph was recently shown, in this current study, we proved for the first time, via HR-PXRD, that the nucleotides can get incorporated into the vaterite crystal lattice, and induce anisotropic lattice strain. This strain is manifested by an expansion along the c -axis and a contraction along the a -axis of the hexagonal vaterite unit cell.…”
Section: Discussionsupporting
confidence: 65%
“…The rhombohedral calcite could be produced through the reaction of CaCl 2 with Na 2 CO 3 , (NH 4 ) 2 CO 3 , NaHCO 3 , and NH 4 HCO 3 in solutions. 1,3,45 However, Mg 2+ ions affect not only the morphology but also the pleomorphism of CaCO 3 , owing to which it is easy for the crystalline surface of calcite to absorb Mg 2+ ions to compete with Ca 2+ to occupy the lattice position, further hindering the crystal growth of CaCO 3 , especially Mg 2+ more than 0.5 mmol L À1 in the reaction solution. 4,46,47 But Mg 2+ concentration in biogas slurry was less than 0.5 mmol L À1 in this study.…”
Section: Preparation Of Ncc With a Bleaching Methods And A Burning Me...mentioning
confidence: 99%